A natureza e a região na Amazônia: zoneamento ecológico-econômico e políticas de desenvolvimento regional - Anna Carolina de Abreu Coêlho; Rafael Gonçalves Gumiero; Sergio Moreno Redón; Andréa Regina de Britto Costa Lopes (Confins)
The aim is to understand nature and region in the Amazon, discussing the possibilities and limits of ecological-economic zoning and regional development policies. From an interpretation of space-time relations in the Amazon, developing narratives and representations of the time and debating more recent scientific analyzes, it is sought to think about the alternatives and the implications put in the perspective of the environmental problematic about sense of the regional question, that minimally mitigate the social, economic and cultural inequalities that persist and deeply mark the humid tropics.